Optimizing conditions for chromium-mediated photo-Fenton-like reactions using design of experiments - Del Pópolo Grzona, Mariana; Orden, Alejandro A.; Lima, Karla V. Leite [UNESP]; De Jesus, Jany H. Ferreira [UNESP]; Leporati, Jorge L.; Pupo Nogueira, Raquel F. [UNESP]; Barbero, Bibiana P. (Elsevier, 2025)
This study aims to utilize the chromium present in tannery wastewaters as a catalyst of photo-Fenton-like reaction. Gallic acid (GA), a monomer of tannic acid, was chosen as a model compound due to its recalcitrance and toxicity. A 2k factorial design followed by a central composite design was applied to evaluate the effects of H2O2 and Cr(III) concentrations, and pH on total organic carbon (TOC) removal. Statistical analysis showed all variables significantly influenced TOC removal, developing a second-order polynomial model (R2 = 0.8502, Radj2 = 0.7967, F-value = 15.89, p-value < 0.0001, lack of fit = 0.24). The most favorable conditions were [H2O2] > 35 mM, [Cr(III)] > 130 mg L−1, and pH 6.5–7.0, achieving up to 26 % TOC removal in 120 min. UV–vis and LC-MS confirmed GA degradation; although, the byproducts generated would be very recalcitrant or would inhibit the catalytic action of Cr(III), limiting the TOC removal.
Keywords: Central composite design; Cr(III)-photo-Fenton-like reaction; Full factorial design; Gallic acid degradation; Response surface methodology